Relationship between dental caries level and quality of life of communities aged 35-44 years in South Daha District, South Hulu Sungai Regency - Fatma, Sonya; Hamdani, Riky; Purwaningayu, Juli Harnida (Majalah Kedokteran Gigi Indonesia, 2023)
Dental caries is the most common dental and oral health problem worldwide, including in Indonesia. Dental caries can be caused by a person’s decreased level of productivity, and severe dental caries can cause pain and difficulty eating and sleeping, thus affecting the quality of life. This study aims to determine the relationship between the level of dental caries and the quality of life of people aged 35-44 years in Daha Selatan District, Hulu Sungai Selatan Regency, South Kalimantan Province. This research used analytic observational method with a cross sectional approach. The population of this research was 106 people of South Daha District aged 35-44 years who were selected using simple random sampling technique. The results of statistical analysis using the Chi-square test obtained a significance value of 0.012 (p < 0.05), indicating a significant correlation between the level of dental caries and the quality of life of 35-44-year-olds. There is a definite need for increasing public awareness of the importance of maintaining oral and dental health to reduce cases of tooth decay caused by dental caries and improve people’squality of life.